Synthesis and Properties of UV-Curable Polyurethane Acrylate with Star-Shaped Structure - Yuan, Lihua; Wang, Ming; Zhang, Xixiang; Chen, Deben; Zhong, Anyong (Asian Journal of Chemistry, 2012)
Novel UV-curable polyurethane acrylate with star-shaped structure is synthesized by using trimethylolpropane as the core and polybutylene adipate as flexible arms. The chemical structure of polyurethane acrylate oligomer is identified by nuclear magnetic resonance and Fourier transform infrared spectra. Molecular weight and molecular weight distribution are measured by gel permeation chromatography. The rheological behaviour of polyurethane acrylate oligomer and mechanical properties of cured film are also investigated.